Evidence for the replication of a plant rhabdovirus in its arthropod mite vector - Hideki Kondo; Miki Fujita; Paul Telengech; Kazuyuki Maruyam; Kiwamu Hyodo; Aline Daniele Tassi; Ronald Ochoa; Ida Bagus Andika; Nobuhiro Suzuki (Virus Research)
Transmission of plant viruses that replicate in the insect vector is known as persistent-propagative manner. However, it remains unclear whether such virus-vector relationships also occur between plant viruses and other biological vectors such as arthropod mites. In this study, we investigated the possible replication of orchid fleck virus (OFV), a segmented plant rhabdovirus, within its mite vector (Brevipalpus californicus s.l.) using quantitative RT-qPCR, western blotting and next-generation sequencing. Time-course RT-qPCR and western blot analyses showed an increasing OFV accumulation pattern in mites after virus acquisition. Since OFV genome expression requires the transcription of polyadenylated mRNAs, polyadenylated RNA fractions extracted from the viruliferous mite samples and OFV-infected plant leaves were used for RNA-seq analysis. In the mite and plant datasets, a large number of sequence reads were aligned to genomic regions of OFV RNA1 and RNA2 corresponding to transcribed viral gene mRNAs. This includes the short polyadenylated transcripts originating from the leader and trailer regions at the ends of the viral genome, which are believed to play a crucial role in viral transcription/replication. In contrast, a low number of reads were mapped to the non-transcribed regions (gene junctions). These results strongly suggested that OFV gene expression occurs both in mites and plants. Additionally, deep sequencing revealed the accumulation of OFV-derived small RNAs in mites, although their size profiles differ from those found in plants. Taken together, our results indicated that OFV replicates within a mite vector and is targeted by the RNA-silencing mechanism.